MAP(ASH): A new scoring system for the prediction of intervention and mortality in upper gastrointestinal bleeding. Issue 1 (19th August 2019) - Redondo‐Cerezo, Eduardo; Vadillo‐Calles, Francisco; Stanley, Adrian J; Laursen, Stig; Laine, Loren; Dalton, Harry R; Ngu, Jing H; Schultz, Michael; Jiménez‐Rosales, Rita
Abstract: Background and Aim: Risk stratification for upper gastrointestinal bleeding (UGIB) is recommended. However, scoring system accuracy is suboptimal, and score calculation can be complex. Our aim was to develop a new score, the MAP(ASH) score, with information available in the emergency room and to validate it. Methods: The score was built from a prospective database of patients with UGIB and validated in an international database of 3012 patients from six hospitals. Outcomes were 30‐day mortality, endoscopic intervention, any intervention (red blood transfusion, endoscopic treatment, interventional radiology, surgery, or death), and rebleeding. Accuracy to predict outcomes was assessed by the area under the receiver operating characteristic curve (AUROC). Results: Five hundred forty‐seven patients were included in the development cohort. Impaired mental status, albumin < 2.5 g/dL, pulse > 100, American Society of Anesthesiologists score > 2, systolic blood pressure < 90 mmHg, and hemoglobin < 10 g/dL were included in the score. The model had a good predictive accuracy for intervention (AUROC = 0.83; 95% confidence interval [CI]: 0.79–0.88) and fair for mortality (AUROC = 0.74; 95% CI: 0.68–0.81). Regarding endoscopic intervention, AUROC was 0.61 (95% CI: 0.56–0.66) in the original cohort and 0.69 (95% CI: 0.66–0.71) in the validation cohort, showing a poor performance, similar to other scores. For rebleeding, the MAP(ASH) (AUROC 0.73; 95% CI: 0.69–0.77) was similar to Glasgow Blatchford score (AUROC = 0.72; 95% CI: 0.67–0.76) but superior to AIMS65 (AUROC = 0.64; 95% CI: 0.59–0.68). Conclusion: MAP(ASH) is a simple pre‐endoscopy risk score to predict intervention after UGIB, with fair discrimination at predicting mortality. Because of its applicability, it could be an option in clinical practice.